2009
DOI: 10.1007/s00415-009-5421-y
|View full text |Cite
|
Sign up to set email alerts
|

Microembolic signals in systemic lupus erythematosus and other cerebral small vessel diseases

Abstract: Microembolic signals (MES) are detected by transcranial Doppler (TCD), and are mainly observed in cardiac and large-artery diseases; however they might also be observed in conditions affecting small vessels of the brain. We aimed to review the current medical literature related to MES assessed by TCD in patients with cerebral small vessel disease. We conducted a systematic review in PubMed and selected the articles with information on this topic. Systemic lupus erythematosus (SLE) is the disease with more arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
(69 reference statements)
2
10
0
Order By: Relevance
“…TCD is a sensitive, real-time monitor of cerebral blood flow velocity (CBFV) and emboli. 9 The present study was conducted to clarify issues regarding 1) the prevalence of neuropsychiatric disorders in a randomly selected group of SLE patients with or without manifest neuropsychiatric symptoms, 2) the early appearance of cerebrovascular changes in SLE patients by usage of transcranial duplex imaging to assist internal cerebral blood vessels. In addition, to determine the relation between transcranial duplex findings of different intracranial vessels with systemic, neuropsychiatric symptoms cognitive function and Systemic Lupus Erythematosus Disease Activity Index (SLEDAI).…”
Section: Introductionmentioning
confidence: 99%
“…TCD is a sensitive, real-time monitor of cerebral blood flow velocity (CBFV) and emboli. 9 The present study was conducted to clarify issues regarding 1) the prevalence of neuropsychiatric disorders in a randomly selected group of SLE patients with or without manifest neuropsychiatric symptoms, 2) the early appearance of cerebrovascular changes in SLE patients by usage of transcranial duplex imaging to assist internal cerebral blood vessels. In addition, to determine the relation between transcranial duplex findings of different intracranial vessels with systemic, neuropsychiatric symptoms cognitive function and Systemic Lupus Erythematosus Disease Activity Index (SLEDAI).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was demonstrated that duplex sonography of intracranial vessels is able to individuate patients with microembolic causes of NPSLE (13,14); in our NPSLE group of patients, nobody had microembolic disease but other causes, all meeting the Hocheberg's modified ACR nomenclature (17), were implicated. This heterogeneity of causes might be a reason why ultrasound is not able to differentiate patients with NPSLE from the others without neuropsychiatric manifestations.…”
Section: Discussionmentioning
confidence: 82%
“…Little information is available on the role of ultrasound in evaluating carotid and cerebral arteries in SLE. The importance of transcranial Doppler sonography was interestingly shown by some studies that correlated the presence of microembolic signals with neuropsychiatric disorders in SLE (13,14). Therefore, our aim was to evaluate internal carotid and middle cerebral arteries by means of duplex sonography in healthy control subjects and in NPSLE compared to other SLE patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microembolic signals in medium-sized arteries have been described in SS patients. 6 Finally, the baseline CBV was relatively preserved, which may be associated with a favorable clinical response after treatment with rt-PA.…”
Section: Discussionmentioning
confidence: 99%